Molecular cloning and analysis of SSc5D, a new member of the scavenger receptor cysteine-rich superfamily. - Gonçalves, C; Castro, M; Henriques, T; Oliveira, M; Pinheiro, H; Oliveira, C; Sreenu, V; Evans, E; Davis, S; Moreira, A; Carmo, A (2009)
Glycoproteins of the scavenger receptor cysteine-rich (SRCR) superfamily contain one or more protein modules homologous to the membrane-distal domain of macrophage scavenger receptor I. These domains can be found in the extracellular regions of membrane proteins and in secreted glycoproteins, from the most primitive species to vertebrates. A systematic, bioinformatics-based search for putative human proteins related to the forty-seven known human group B SRCR domains identified a new family member that we have called Soluble Scavenger with 5 Domains (SSc5D). SSc5D is a new soluble protein whose expression is restricted to monocytes/macrophages and T-lymphocytes, and is particularly enriched in the placenta. The gene encoding SSc5D spans 30kb of genomic DNA, and contains fourteen exons producing a 4.8kb-long mRNA. The mature polypeptide is predicted to consist of 1573 amino acids comprising, towards the N-terminus, five very similar SRCR domains that are highly conserved among non-marsupial mammals, and a large (>250nm), very heavily glycosylated, mucin-like sequence towards the C-terminus. Each of the SRCR domains is encoded by a single exon, and contains eight cysteine residues, as observed for all other group B SRCR domains. A shorter isoform encoded by a weakly expressed, alternatively spliced transcript, which lacks the mucin-like C-terminal region, was also identified. It seems likely that SSc5D has a role at the interface between adaptive and innate immunity, or in placental function.